PENGARUH KEMAMPUAN KERJA, PERSYARATAN JABATAN DAN KOMITMEN TERHADAP KINERJA KARYAWAN PADA PT. BENAWA CITRA PUTRA TABALONG - Hardi Pramana Putra (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
The purposes of this study are: (1) To know the effect of work ability on the performance of employees at PT. Benawa Citra Putra Tabalong. (2) To know the effect of position requirements on the performance of employees at PT. Benawa Citra Putra Tabalong. (3) To know the effect of commitment to the performance of employees at PT. Benawa Citra Putra Tabalong. (4) To know the effect of work ability, Position Requirements and Commitments simultaneously on the performance of employees at PT. Benawa Citra Putra Tabalong. This study used descriptive quantitative method. The sample of population were 40 employees. The instrument used to collect the data was questionnaire. Data were analyzed by using SPSS version 20. Result of the study shows that : (1) The work ability has a significant effect on the performance of employees at PT Citra Putra Tabalong Benawa Tabalong, it amounts 67.1% (2) The position requirements has a significant effect on the performance of employees at PT Citra Putra Tabalong Benawa Tabalong, it amounts 23.5% (3) Commitment has an effect on the performance of employees at PT Citra Putra Tabalong Benawa Tabalong, it amounts 31.4% (4) Work Ability, Position Requirements and Commitments simultaneously have a significant effect on the performance of employees at PT Citra Putra Tabalong Benawa District, Tabalong regency, it amounts 67.9%.